2013
DOI: 10.1186/1757-7241-21-43
|View full text |Cite
|
Sign up to set email alerts
|

Emergency cricothyrotomy – a systematic review

Abstract: BackgroundAn emergency cricothyrotomy is the last-resort in most airway management protocols and is performed when it is not possible to intubate or ventilate a patient. This situation can rapidly prove fatal, making it important to identify the best method to establish a secure airway. We conducted a systematic review to identify whether there exists superiority between available commercial kits versus traditional surgical and needle techniques.MethodsMedline, EMBASE and other databases were searched for pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 49 publications
(65 reference statements)
3
110
0
5
Order By: Relevance
“…Several techniques have been described for emergency open surgical cricothyroidotomy: as per Advanced Trauma and Life Support (ATLS); Bair Claw device [20]; rapid four-step technique [21]; bougie-assisted emergency cricothyroidotomy [7] and cricothyroidotomy scissor [22]. No significant difference in success rates was found in a recent systematic review [12]. In this study, we deliberately did not specify any particular technique, leaving the participant to use their preferred technique.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several techniques have been described for emergency open surgical cricothyroidotomy: as per Advanced Trauma and Life Support (ATLS); Bair Claw device [20]; rapid four-step technique [21]; bougie-assisted emergency cricothyroidotomy [7] and cricothyroidotomy scissor [22]. No significant difference in success rates was found in a recent systematic review [12]. In this study, we deliberately did not specify any particular technique, leaving the participant to use their preferred technique.…”
Section: Discussionmentioning
confidence: 96%
“…Several have employed a similar methodology to ours [4,9], and the porcine model has been shown to provide both a realistic anatomical representation of the human airway [10] and a useful training tool for cricothyroidotomy [11]. These studies have revealed conflicting success rates, insertion times and safety profiles, and a recent systematic review discussed how no particular device had any clear advantage over the others [12]. NAP4 gives us some data regarding successful outcomes with patients in real life emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results also indicated increased success rates and quicker procedure times with the open surgical technique [16,19]. A review on the topic was not able to demonstrate a significant difference between open surgical and needle-guided methods because of the limited number of patients assessed [6].…”
Section: Discussionmentioning
confidence: 91%
“…(needle or open) [6]. Dutch ambulance nurses are not legally allowed to use drugs to facilitate intubation.…”
Section: Introductionmentioning
confidence: 99%
“…La mise en place d'une canule de Guédel est possible, mais pas obligatoire. Si la subluxation est insuffisante, le médecin peut réaliser en sauvetage une cricothyroïdotomie ou coniotomie [8]. En cas de troubles de ventilation, lorsque celui-ci est en rapport avec un pneumothorax suffocant (silence auscultatoire) dans un contexte de traumatisme thoracique, l'exsufflation est urgente.…”
Section: Données éPidémiologiquesunclassified